Designing of double-threaded intramedullary pin and evaluation of ex vivo biomechanical resistance to axial compression load on the canine long bone fracture gap model - Vora, Shruti; Kumar, Ashwani; Kaur, Kirandeep (The Indian Journal of Animal Sciences, 2022)
Intramedullary (IM) pinning is a biological method of fracture fixation; but is associated with complications of pin migration, proximal fragment collapse and rotational instability. The study aimed to design double threaded (DT) IM pin and evaluated its biomechanical resistance to axial compression load in comparison to end-threaded (ET) and simple Steinman (SS) IM pin on the canine long bone fracture gap model. The DT IM pin was designed considering various morphometric measurements (17 femur and 8 tibia bones) on lateral radiographs of the routinely done healthy dogs. For ex vivo biomechanical study, a distal third fracture was created in the 17 (8 femoral, 9 tibial) canine cadaveric bones. A normograde IM pinning using SS, ET and DT was done keeping atleast 10 mm gap at the fracture site (fracture gap-model). A pin occupying 60-70% of the narrowest medullary canal was used for ET and DT, and >80% for SS models. The bone-implant constructs were subjected to axial compression load (N) till 5 mm displacement of the proximal bone fragment or till dislodgement of the implant using 0.5 mm/min velocity on a servo-hydraulic testing machine. The magnitude of the axial compression load/mm displacement was influenced by the bone (femur vs tibia) and implant types. In femur, the DT pins sustained higher compression loads followed by SS and ET. However, for tibia, the load required was highest with DT followed by ET and SS pin. The study reports the first of its kind indigenously designed biomechanically superior double threaded pin for the canine long bone fracture fixation